2020
DOI: 10.14701/ahbps.2020.24.3.283
|View full text |Cite
|
Sign up to set email alerts
|

A single institution experience with robotic and laparoscopic distal pancreatectomies

Abstract: Backgrounds/Aims: This study aims to describe our experience with minimally-invasive distal pancreatectomies, with emphasis on the comparison between robotic distal pancreatectomy (RDP) and laparoscopic distal pancreatectomy (LDP). Methods: Retrospective review of 102 consecutive RDP and LDP from 2006 to 2019 was performed. Results: There were 27 and 75 patients who underwent RDP and LDP, respectively. There were 12 (11.8%) open conversions and 16 (15.7%) patients had major (>grade 2) morbidities. Patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…There is no surgical mortality in both RDP and LDP groups in our series. Many authors also reported similar findings like ours 3,12,14,16,27,28 . Technically, RDP and LDP are comparable in terms of feasibility and safety.…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…There is no surgical mortality in both RDP and LDP groups in our series. Many authors also reported similar findings like ours 3,12,14,16,27,28 . Technically, RDP and LDP are comparable in terms of feasibility and safety.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, when choosing the type of MIS adopted, the cost would be a major factor to consider if patients had to pay an additional amount for robotic surgery. Although the cost of robotic surgery could vary between institutions and countries, nevertheless, it is uniformly higher than conventional laparoscopic surgery 27 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations